Central banks and coded language : risks and benefits - Muchlinski, Elke. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
The book deals with the implications and consequences of the modern view of central banks. It focuses on coded language in order to explain why a central bank's decisions and communicative interactions cannot be devoted to an artificially created coded language.
Includes bibliographical references and index.
rua 30/10/13
Loans
Keywords: Banks and banking, Central; Communication; Transparency in government